Application of water treatment sludge in degraded soil - Teixeira, Sandra Tereza; Melo, Wanderley José de; Silva, Érica Tome da (Pesquisa Agropecuaria Brasileira, 2005)
The application of water treatments sludge (WTS) in degraded soil is an alternative solution for this residual disposal and also for degraded soil recuperation. The objective of this work was to evaluate the effect of application of WTS in content of macronutrients, total organic carbon (TOC) and electric conductivity (EC) in degraded soil by tin mining. The WTS can be used in degraded area, because it increases the contents of Ca, Mg, K and soil pH.
Keywords: salinity; mining; electric conductivity; solid residue; total organic carbon